Analisis Gas Buang Insinerator dengan Filter Arang Aktif Berbasis Limbah Organik - Fajriyah Rafidah; Fitriyanti; Kurniati Abidin (Jurnal Teori dan Aplikasi Fisika, 2025)
This study aims to analyze the effectiveness of organic waste-based activated charcoal in filtering flue gas from incinetors. With the increasing volume of solid waste and the negative impact of harmful gas emissions, it is important to find sustainable and environmentally friendly solutions. The activated charcoal used in this study is produced from agricultural waste, namely corn cobs and candlenut shells, which are abundant and can be optimally utilized. The analytical method applied includes measuring exhaust gas levels before and after filtration using activated charcoal. Measurements were made to identify the concentration of various pollutants, including carbon monoxide (CO) and sulfur dioxide (SO2), which are known as harmful gases to human health and the environment. The data obtained shows that without a filter, the concentration of CO is 0 ppm and SO2 is 473 ppm, while after using the activated carbon filter, the concentration of CO increases to 2.775 ppm and SO2 decreases to 56 ppm. For nitrogen dioxide (NO2), the concentration remains 0 ppm both before and after filtration. The results indicated that the use of activated charcoal can significantly reduce the concentration of these harmful gases, with varying degrees of efficiency depending on the type waste used as raw material. This research provides valuable insights into the utilization of organic waste as a solution in air pollution control. In addition, the results are expected to encourage the development of more efficient filtration technologies utilizing local resources. Thus, this research not only contributes to waste management, but also to overall environmental protection. Keywords: incinerator, activated charcoal, organic waste, flue gas filtration, air pollution.